1997
DOI: 10.1038/sj.bjp.0701382
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin A‐LI release after antigen challenge in guinea‐pig bronchial tubes: influence of histamine and bradykinin

Abstract: 1 Our aim was to determine if antigen challenge stimulates sensory nerves and provokes the release of tachykinins. The involvement of histamine and bradykinin was studied by using speci®c receptor antagonists. Capsaicin-induced responses were also examined. Experiments were performed in vitro on tracheal and bronchial preparations from ovalbumin-sensitized guinea-pigs. 2 Characterization of ovalbumin-induced contraction, with regard to histamine and bradykinin, was carried out on airway ring preparations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Both preparations are in vitro models for acute, mast cell‐driven, antigen‐induced, contractions and the mediators of these contractile responses ( Jonsson and Dahlén, 1994 ) are those established for the anaphylactic contraction of human airways in vitro and in vivo , namely histamine and leukotrienes ( Björck and Dahlén, 1993 ; Roquet et al ., 1997 ). In the trachea, the histamine component of the antigen‐induced contraction dominates ( Lindstrom and Andersson, 1997 ), whereas in the GPLP, antihistamines alone have no inhibitory effect on the antigen‐induced contraction ( Jonsson and Dahlén, 1994 ). It was hypothesized that interactions between a H1 histamine receptor antagonist and a NO‐donor thus effectively could be evaluated in the antihistamine‐sensitive GPT.…”
Section: Discussionmentioning
confidence: 99%
“…Both preparations are in vitro models for acute, mast cell‐driven, antigen‐induced, contractions and the mediators of these contractile responses ( Jonsson and Dahlén, 1994 ) are those established for the anaphylactic contraction of human airways in vitro and in vivo , namely histamine and leukotrienes ( Björck and Dahlén, 1993 ; Roquet et al ., 1997 ). In the trachea, the histamine component of the antigen‐induced contraction dominates ( Lindstrom and Andersson, 1997 ), whereas in the GPLP, antihistamines alone have no inhibitory effect on the antigen‐induced contraction ( Jonsson and Dahlén, 1994 ). It was hypothesized that interactions between a H1 histamine receptor antagonist and a NO‐donor thus effectively could be evaluated in the antihistamine‐sensitive GPT.…”
Section: Discussionmentioning
confidence: 99%
“…Sample preparation and neurokinin A radioimmunoassay were performed as described previously (Lindstrom and Andersson, 1997;Grider, 2003) with minor modification. After equilibration, the muscle strips were rinsed three times with fresh Krebs' solution.…”
Section: Methodsmentioning
confidence: 99%
“…(1995) reported that plasma extravasation and substance P release was suppressed in burn wounds in kininogen‐deficient rats. Furthermore, in other models of experimental inflammation, it has been reported that inducible B 1 (Ferreira et al ., 2000) and constitutive B 2 receptors (Ricciardolo et al ., 1994; Lindstrom & Andersson, 1997; Schuligoi et al ., 1998) mediate tachykinin release from afferent sensory neurons. Taken together, we conclude that a similar interaction may occur in thermally injured tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However in NK 1 receptor knockout mice, the kinin antagonists were without effect (Cao et al ., 2000). Indeed, evidence for a link between the tachykinin and kinin receptors has been produced in several models of inflammation (Ricciardolo et al ., 1994; Lindstrom & Andersson, 1997; Schuligoi et al ., 1998; Ferreira et al ., 2000). In addition, studies in the microvasculature of neutral endopeptidase knockout mice have revealed that spontaneous plasma leakage is inhibited by treatment with NK 1 and kinin B 2 antagonists (Lu et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%